Analisis Tingkat Pengetahuan Ibu Rumah Tangga Tentang Jenis Dan Bahaya Plastik Kemasan Makanan Di Wilayah Kerja Puskesmas Sungai Besar Kota Banjarbaru Tahun 2012 - Isnawati Isnawati (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2014)
Abstract: Analysis Of Knowledge About The Housewife And Dangers Of Plastic Food Packaging In The Region “Puskesmas Sungai Besar” Banjarbaru Cyty In 2012. Banjarbaru ranks second in South Kalimantan in terms of degenerative diseases (RISKESDA, 2007). Not a few in this town of outstanding products especially plastic packaging used for food, how did the mother know the type of plastic household and trying to protect their families from products that endanger the health of their families. This study aims to determine the level of knowledge about the type Housewife and Hazard plastic food packaging in the region of the Puskesmas Sungai Besar Banjarbaru City with methods of descriptive and cross-sectional approach, the 68 housewives. Education levels housewife in Puskesmas Sei. Besar 44.1% had graduated from high school. Sources of information about the types of food packaging 51.5% came from television and radio, and the other from a friend, neighbor, print media and school/ college. Housewife knowledge about the dangers of plastic food packaging 75% of the radio and television and on the type of plastic food packaging low. Only 1.5% who know the type of plastic in the market. Plastics are not eligible yet many (54.5%) are known to housewives. The level of knowledge Housewife In Puskesmas Sei. Besar about the type of food packaging mostly low, so about the dangers of plastics used as food packaging. Types of plastics for food packag-ing are widely circulated, still wise in choosing the type of plastic to avoid the danger caused. Keywords: plastic; knowledge; danger; packaging